Longing for the Past and Longing for the Future: A Phenomenological Assessment of the Relation Between Temporal Focus and Readiness to Change Among People Living With Addiction - Salmon, Melissa M.; Wohl, Michael J. A. (Frontiers in Psychology, 2020)
At present, the dominant motivational strategy to facilitate behavior change among those living with addiction is to focus one’s attention on the better possible future that may result from cutting down or cessation. However, research is now emerging that suggests nostalgic reverie (i.e., sentimental longing) for life lived before addiction can also motivate behavior change. In the current research, we explore the conditions in which longing for a better future free of addiction and longing for one’s past that was free of addition might motivate change. To this end, we assessed first-person experiential narratives of problem gamblers to better understand how they feel about their past or future without gambling, and how those feelings may relate to motivation to change. Problem gamblers were randomly assigned to either write about their lived past before gambling (n = 31) or their expected future without gambling (n = 26). Each narrative was systematically examined to identify recurrent themes and cluster these narratives according to similarly expressed themes. In the past condition, participants reported their life before gambling was either positive (Cluster P1) or difficult (Cluster P1). Gamblers with a positive past described how their life, character, close relationships, and the activities they engaged in before gambling were more meaningful. Importantly, these gamblers also reported feeling more nostalgic for life without gambling and were more ready to change their behavior than gamblers with a difficult past. In the future condition, participants were either positive (Cluster F1) or ambivalent (Cluster F2) about a future free from gambling. Gamblers who expected a positive future described how they expect their emotions, finances, and the activities they will engage in to be more positive without gambling. Compared to those ambivalent about their future, these gamblers also reported a future without addiction to be more vivid and had more desire to change their behavior, but there were no between-cluster differences in readiness to change. These findings demonstrate unique differences in how gamblers perceive their past and future without gambling, and shed a novel light on how each temporal focus might motivate behavior change among those living with addiction.